Islamic Banking and Financing Models in the Islamic Bank - Budimir, Nemanja (Oeconomica Jadertina, 2017)
Islamic banking is now a widespread notion in both Islamic countries and the West. It denotes a bank form and finances that seek to provide services to clients without interest. Proponents of Islamic banking say that the main objective is the "fish", which is prohibited by Islamic law. This attitude toward interest contributed to the unification of several Islamic schools, with the aim of finding ways for the development of an alternative banking system that would be compatible with the rules of Islamic Laws, and in particular to the rules relating to the prohibition of interest. Since the mid-1970s, the number of Islamic banks is on the rise. Islamic banks are not only based in countries where Islam is the prevalent religion, such as Egypt, Jordan, Sudan, Bahrain, Kuwait, United Arab Emirates, Tunisia, Mauritania and Malaysia, but also in countries such as the UK, Germany and the Philippines where Islam is a minority religion. The International Islamic Bank, the Islamic Development Bank, whose shareholders are members of the Islamic Conference Organization are acting as sponsors for Islamic banking and finance throughout the Islamic world.